Multivitamin Supplementation and Fertility Outcome: A Retrospective Single-Center Cohort Study and the Clinical and Medicolegal Value of Nutritional Counseling - Giuseppe Gullo; Simona Zaami; Adriana Vita Streva; Sofia Burgio; Valentina Billone; Yulia Kotlik; Elena Chitoran; Silvia Ganduscio; Giovanni Baglio; Antonio Perino; Gaspare Cucinella (Life)
Resveratrol can beneficially affect growth and follicle development and lead to improved sperm function parameters in pre-clinical studies, while information from clinical studies is still inconclusive. This study aims to evaluate the biological and clinical impact of a resveratrol-based multivitamin supplement on level II assisted reproduction cycles (IVF and intracytoplasmic sperm injection [ICSI]). A retrospective, case-control study, involving 70 infertile couples undergoing IVF/ICSI cycles, was conducted at the Assisted Reproductive Center, Obstetrics and Gynecology Unit-Villa Sofia-Cervello Hospital in Palermo. The study group underwent pre-treatment with a daily nutraceutical based on resveratrol, whereas the control group received 400 mcg/day of folic acid. Primary endpoints to be evaluated were the number of mature follicles developed (>16 mm), total oocytes and Metaphase II (MII) oocytes retrieved, fertilization rate, number of embryos/blastocysts obtained, and semen quality. Secondary objectives in our evaluation were the duration and dosage of gonadotropins, the starting dose, the number of blastocysts to be transferred and frozen, implantation rate, and, ultimately, biochemical and clinical pregnancy rates. In the study group, a significantly higher number of mature follicles, oocytes, and MII oocytes were collected compared to the control group. In the study group, a higher fertilization rate as well as higher numbers of cleavage embryos per patient, blastocysts per patient, and frozen blastocysts were obtained. In the study group, a shorter administration time and lower dosages of gonadotropins required to reach follicle maturity were also observed compared to controls, with fewer dose adjustments during stimulation compared to the starting dose. No significant differences were found in biochemical or clinical pregnancy rates. A 12-month period of dietary supplementation with a resveratrol-based multivitamin nutraceutical leads to better biological effects on ICSI cycles.